2011
DOI: 10.3171/2011.1.jns101326
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically guided epidural blood patch with subsequent spinal CT scans in the treatment of spontaneous cerebrospinal fluid hypovolemia

Abstract: The results indicated that fluoroscopically guided EBP and subsequent spinal CT scans may provide a highly effective therapy in patients with SCH proven on CT myelography studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
(32 reference statements)
0
16
0
1
Order By: Relevance
“…To the best of our knowledge, the detailed analysis of CT myelography, which is less invasive and can be performed easily on a routine basis, has yet to be described in the literature. 2,8,[16][17][18] The study reported here raises the following 4 points with regard to the diagnosis and treatment of spontaneous CSF leaks. First, EBP at the level near the spinal lesions resulted in good outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the detailed analysis of CT myelography, which is less invasive and can be performed easily on a routine basis, has yet to be described in the literature. 2,8,[16][17][18] The study reported here raises the following 4 points with regard to the diagnosis and treatment of spontaneous CSF leaks. First, EBP at the level near the spinal lesions resulted in good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of targeted EBP is increasingly being reported, previous studies have not described in detail how to determine the leak site and target the spinal level for EBP. 8,[16][17][18] A common cause of CSF leaks is considered to be a ventral dural defect or meningeal diverticulum at the dural root sleeves. 3 In terms of leakage detection, the diagnostic method with the highest sensitivity is CT myelography.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Thus, only a few reports of targeted EBPs exist in the literature. [11][12][13][14][15] In contrast to a blind EBP, a targeted EBP relies on an accurate localization of the leakage site. To this end, several imaging techniques are available, including CT myelography, radioisotope cisternography, and MR imaging of the spine.…”
mentioning
confidence: 99%
“…9 Prior authors have reported symptomatic improvement rates ranging from 50% to 100% with site-directed epidural blood/fibrin patch procedures by using CT or fluoroscopic guidance. [10][11][12][13][14][15] These treatment options, however, often require epidural punctures in the upper thoracic and cervical spine. Epidural puncture in these regions is technically more challenging due the anatomy and the epidural space becoming smaller as you ascend from the lumbar to the cervical region.…”
Section: Discussionmentioning
confidence: 99%